Oncofertility in Islam: The Malaysian Perspective - Ahmad, Mohd Faizal; Nik Abdul Ghani, Nik Abdul Rahim; Abu, Muhammad Azrai; Abdul Karim, Abdul Kadir; Shafiee, Mohamad Nasir (Frontiers in Reproductive Health, 2021)
The implementation of oncofertility services is of great importance among cancer survivors of reproductive age to ensure a good quality of life. However, the uptake of this service among Muslim patients is very challenging because of inconclusive laws or evidence based on the Islamic perspective. Hence, we summarized the limited evidence available to consolidate current recommendations for oncofertility practices in the Muslim population in Malaysia. The available “fatwa” and “muzakarah” regarding reproductive procedures and gamete cryopreservation in Islam was searched from the recommendations of local and international bodies, including published and unpublished sources. The relevant information was then extracted according to the current understanding of dilemmas in oncofertility practices in Malaysia, tabulated, and consolidated. Most of the available “fatwa” has been revised by recent “muzakarah” to suit current oncofertility practices. Most Islamic organizations support the practice of oncofertility in Muslim hence indicates that oncofertility services are permissible. Therefore, proper recommendations and counseling are paramount to ensure understanding among Muslim patients.